DISTINGSI DAN TANTANGAN MA’HAD ALY DALAM PUSARAN STANDARISASI: STUDI KOMPARATIF TERHADAP RESPONS MA’HAD ALY ATAS IMPLEMENTASI PMA NO. 32 TAHUN 2020 - Ashoumi, Hilyah; Hamzawi, Mohammad Adib; Yusuf, M Asror; Humaidi, Anis; PS, Alaika M. Bagus Kurnia (STKIP Pesisir Selatan, 2025)
Following the enactment of Ministerial Regulation (PMA) Number 32 of 2020, Ma’had Aly faces a dilemma between maintaining its academic independence and adapting to institutional standards set by the government. In this context, two Ma’had Aly institutions located in Jombang — Ma’had Aly Hasyim Asy’ari Tebuireng and Ma’had Aly Tarbiyatunnasyi’in Pacul Gowang — have shown different responses to the policy. Hasyim Asy’ari emphasizes a systematic academic management in the field of hadith, while Tarbiyatunnasyi’in adopts a cultural and spiritual approach in the cultivation of tasawwuf. As an Islamic higher education institution rooted in the pesantren tradition, Ma’had Aly serves to preserve the continuity of classical Islamic scholarly traditions through the study of turath (classical texts). Unlike conventional Islamic boarding schools, Ma’had Aly has a more structured educational system, complete with academic levels, tracks, and specific fields of specialization. This study aims to examine how Ma’had Aly responds to the demands of formal regulations and the challenges of globalization in the education sector, without losing its identity as an institution devoted to tafaqquh fi al-din (deep understanding of religion).